2005
DOI: 10.1001/archinte.165.20.2420
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Plasma Lipid Levels and Hypertension in Women

Abstract: In this large prospective cohort, atherogenic dyslipidemias were associated with the subsequent development of hypertension among healthy women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
80
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 48 publications
17
80
1
2
Order By: Relevance
“…Additionally, using clinical guideline cut points of lipid measures for prediction of hypertension, both the Women's Health Study and the TLGS highlighted the same association between baseline lipids and incident hypertension. However, in the Sesso et al 15,22 study, levels of HDL-C, non-HDL-C and TC/HDL-C and in the TLGS, levels of HDL-C, TGs and TG/HDL-C were the strongest independent predictors of hypertension, based on popular clinical guidelines.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, using clinical guideline cut points of lipid measures for prediction of hypertension, both the Women's Health Study and the TLGS highlighted the same association between baseline lipids and incident hypertension. However, in the Sesso et al 15,22 study, levels of HDL-C, non-HDL-C and TC/HDL-C and in the TLGS, levels of HDL-C, TGs and TG/HDL-C were the strongest independent predictors of hypertension, based on popular clinical guidelines.…”
Section: Discussionmentioning
confidence: 94%
“…In the Sesso et al 15 study, of 16 130 adult women followed up for 10.8 years, 4593 developed hypertension. In multivariate analyses, the relative risks of incident hypertension from the lowest (referent) to the highest quintile of baseline TC were 1.00, 0.96, 1.02, 1.09 and 1.12 (P ¼ 0.002 for trend); for HDL-C, 1.00, 0.93, 0.87, 0.87 and 0.81 (Po0.001 for trend); for non-HDL-C, 1.00, 1.06, 1.11, 1.12 and 1.25 (Po0.001 for trend); and for the TC/HDL-C, 1.00, 1.10, 1.14, 1.20 and 1.34 (Po0.001 for trend).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8 In addition, our data did not support plasma lipid levels, including total cholesterol, triglyceride, highdensity lipoprotein and low-density lipoprotein cholesterol, as significant predictors for hypertension risk, in contrast to the findings from 16130 women for 10.8 years of follow-up, which showed that hyperlipidemia had a 1.34-fold risk of hypertension. 5 In this Women' Health study, lack of controlling baseline blood pressure and other biochemical variables, such as inflammatory markers and uric acid, may overestimate the role of lipids in the risk of hypertension, although apolipoprotein B, lipoprotein(a) and C-reactive protein were included. 10 Furthermore, the ethnic difference in the metabolic syndrome components should be taken into consideration.…”
Section: Biochemical Risk Factorsmentioning
confidence: 99%
“…Routinely available and easily collected clinical information and lifestyle-related factors have been found to be effective in identifying hypertension risk in prevalent and incident cases. [2][3][4][5][6][7][8] However, the evidence on prediction models providing absolute risk for hypertension risk is relatively scanty and these prediction models have also been developed, primarily in Caucasians. 2,[4][5] Moreover, previous studies based on hypertension prediction models were limited because of short follow-up periods, [3][4]9 an inability to incorporate laboratory data, 4 multiple biomarkers, 10 limited validation 11 and a lack of simple algorithm usage (Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%